Measuring quality performance between public and private hospitals in Malaysia - Ahmed, Selim; Abd Manaf, Noor Hazilah; Islam, Rafikul (Emerald, 2017)
Abstract Purpose – This study aims to measure quality performance of the Malaysian hospitals based on eight items, namely, progress of quality management, medical service cost, reduce errors in medical services, patient waiting time, reduce waste in processes, patient complaint, employee job satisfaction and patient satisfaction. Mainly, it identifies difference or conformance between public and private hospitals on quality performance. Design/methodology/approach – This study distributed 1,007 self-administered survey questionnaires to the hospital staff (i.e. doctors, nurses, pharmacists and medical laboratory technologists), resulting in 438 useful responses (43.5 per cent response rate). Research data were analysed based on descriptive analysis and independent samples’ t-tests using SPSS version 23. Findings – The findings of this study indicate that there are significant differences between public and private hospital staff on progress of quality improvement process, patient satisfaction and cost of the medical services. Private hospital staff believed that their hospital’s quality management process and patient satisfaction has been improved over the past years compared to public hospital. However, private hospital staff does not perceive their medical service cost has been reduced over the past years compared to public hospital. Research limitations/implications – This research focused solely on quality performance of the Malaysian health sector and, thus, the results might not be applicable to other countries. Originality/value – Present research findings provide guidelines for enhancing quality performance in Malaysian public and private healthcare sectors and other countries. Keywords Malaysia, Quality performance, Private hospital, Public hospital Paper type Research paper